2020
DOI: 10.2147/ccid.s239840
|View full text |Cite
|
Sign up to set email alerts
|

<p>Classification and Staging of Morgellons Disease: Lessons from Syphilis</p>

Abstract: Introduction: Morgellons disease (MD) is a contested dermopathy that is associated with Borrelia spirochetal infection. A simple classification system was previously established to help validate the disease based on clinical features (classes I-IV). Methods: Drawing on historical and pathological parallels with syphilis, we formulated a more detailed staging system based on clinical features as well as severity of skin lesions and corresponding histopathological infection patterns, as determined by anti-Borrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…infections, we recognize the importance of coinfections as we and others expand our future studies to include other coinfections and diseases such as Morgellons disease. 42 Importantly, the presence of striae-like skin track lesions in patients presenting with neuropsychiatric symptoms indicate testing for suspected Bartonella spp. infection.…”
Section: Discussionmentioning
confidence: 99%
“…infections, we recognize the importance of coinfections as we and others expand our future studies to include other coinfections and diseases such as Morgellons disease. 42 Importantly, the presence of striae-like skin track lesions in patients presenting with neuropsychiatric symptoms indicate testing for suspected Bartonella spp. infection.…”
Section: Discussionmentioning
confidence: 99%
“…Control staining, as previously described, demonstrated no reactivity to common Gram-positive and Gram-negative organisms, nor was it reactive to fungal-infected human skin specimens or inflamed skin specimens from a patient diagnosed with psoriasis. 14 …”
Section: Methodsmentioning
confidence: 99%
“…4–12 Histological studies have revealed that MD lesions demonstrate hyperplasia and parakeratotic hyperkeratosis, and that the characteristic cutaneous fibers are composed of keratin and collagen originating primarily from keratinocytes within the stratum basale. 13 , 14 Thus, MD fibers are of undeniable human cellular origin and are not manufactured artifacts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations